ADOPSI MERUPAKAN SOLUSI BAGI ANAK JALANAN DALAM PRESPEKTIF HAM - Alwan Hadiyanto (JURNAL DIMENSI, 2013)
Protection and prosperity of children rights have been included in various existing law and regulations. However, the numbers of children that can not go to school still increase since the shortcoming of financial and facilities for school education in many areas Indonesia. Therefore, it’s important to know whether the problems of children who loss their chance for education is a political strategy to grow urban society environment to get the attention of a group of life of middle society towards impecunious society remaining urban, adoption of is a solution for public road children to overcome the needs of education chance in perspective of human rights.